PENGETAHUAN IBU HAMIL TENTANG BAHAYA KOSMETIK BERBAHAN MERCURY KLINIK KURNIA KEC. DELITUA KAB.DELI SERDANG TAHUN 2018 - Kristin Natalia; Husna Sari (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2018)
Currently cosmetics contain many dangerous ingredients circulating in the community. Types of cosmetics that are widely used by pregnant women are mercury products in skin care products and cosmetics that are thought to interfere with the health of the fetus. Often times cosmetics have a negative impact on the health of pregnant women, a problem that often occurs is that the body sweats more easily given the increased metabolic processes in the body. In addition, substances in cosmetics can also inhibit and interfere with fetal development and can even cause miscarriages. The purpose of this study was to determine the knowledge of pregnant women about the dangers of cosmetics made by Mercury at Kurnia Clinic Kec.Delitua Kab.Deli Serdang in 2018. This research was conducted in March, this research was descriptive, data collection through questionnaires containing the characteristics of direct respondents. The population in this study were pregnant women. The sample technique used was Accidental Sampling as many as 20 respondents. The results showed that the knowledge of pregnant women about the dangers of cosmetics made from mercury was less than 2 people (10%), had enough knowledge of 11 people (55%), and had good knowledge of 7 people (35%). It is expected that pregnant women should increase their knowledge about the dangers of cosmetics made from mercury in pregnant women.